2017
DOI: 10.1038/srep46101
|View full text |Cite
|
Sign up to set email alerts
|

Novel miRNA-mRNA interactions conserved in essential cancer pathways

Abstract: Cancer is a complex disease in which unrestrained cell proliferation results in tumour development. Extensive research into the molecular mechanisms underlying tumorigenesis has led to the characterization of oncogenes and tumour suppressors that are key elements in cancer growth and progression, as well as that of other important elements like microRNAs. These genes and miRNAs appear to be constitutively deregulated in cancer. To identify signatures of miRNA-mRNA interactions potentially conserved in essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 87 publications
2
32
0
Order By: Relevance
“…miRNAs regulate many cellular processes such as differentiation, proliferation, migration, and apoptosis . Recent studies have indicated that miRNAs function as oncomiRs or suppressor miRNAs by downregulating cancer suppressor genes or oncogenes . miR‐24‐3p, which belongs to the miR‐24 family, plays a significant role in cancer initiation and progression.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs regulate many cellular processes such as differentiation, proliferation, migration, and apoptosis . Recent studies have indicated that miRNAs function as oncomiRs or suppressor miRNAs by downregulating cancer suppressor genes or oncogenes . miR‐24‐3p, which belongs to the miR‐24 family, plays a significant role in cancer initiation and progression.…”
Section: Introductionmentioning
confidence: 99%
“…Andrés-León et al [12] analyzed miRNAs in The Cancer Genome Atlas (TCGA) data for HCC and other tumor types. In 2018, a study integrated miRNA expression database (TCGA, GSE31384 [13] , and GSE6857 [14] ) and compared their expression in liver cancer and adjacent normal samples to investigate the difference of miRNAs expression associated with carcinogenesis [15] .…”
Section: Mirna Expression Profiles In Hccmentioning
confidence: 99%
“…In a recent study, the transcriptome of 15 of the most common tumor subtypes was analyzed. 80 the study identified differential expression of 147 genes and 95 miRNAs that were shared in most tumor types. Importantly, 36 paired interactions between the miRNA and the reported targeted transcript were deregulated together.…”
Section: Limitations Of Conventional Cancermentioning
confidence: 99%
“…this result indicates that a single dysregulated miRNA can alter the expression of its target genes, and that these altered mRNA-miRNA interactions are conserved in cancer pathways between various tumors. 80 therefore, balancing the levels of miRNAs that are dysregulated in cancer, through miRNA-based therapeutic approaches, can potentially impact multiple major signaling pathways in carcinogenesis.…”
Section: Limitations Of Conventional Cancermentioning
confidence: 99%